Pertanian dalam Perspektif Al-Qur’an - Suhdan Kasuba; Ahmad Abubakar; Hasyim Hadede (Journal on Education, 2023)
Agriculture is the activity of raising crops and livestock on a plot of land, without causing the land to be damaged for further production. Besides that, agriculture cannot be separated from plants grown by humans, but growth cannot be separated from the intervention of Allah SWT. Because the Qur'an is a book of guidance for humans in all matters, whose authenticity is guaranteed. Indeed, the Qur'an is not a scientific book, but a religious book. Even so, it cannot be denied that it contains many natural cues. The Qur'an contains verses that discuss science, including agriculture, which are very numerous. Therefore, in this study, the author tries to reveal interpretations related to these verses. The results of this study show that by studying the Koran we are able to explain verses about agriculture in a comprehensive manner, even explaining different things about agriculture in one verse or a combination of verses. Besides that, we can also know about different soil conditions, therefore by studying Agriculture it is necessary to understand agriculture in the context of the Qur'an as a guide for mankind in the world and in the hereafter. Thus, these blessings will bring good agricultural results. overflow.